2017
DOI: 10.1111/jace.14850
|View full text |Cite
|
Sign up to set email alerts
|

Niobium and divalent‐modified titanium dioxide ceramics: Colossal permittivity and composition design

Abstract: Colossal permittivity (CP) (e r =10 4~1 0 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…A conventional process typically used to increase the dielectric permittivity is by introducing electrical conductivity or incorporating conductive fillers into the polymer matrix to form a composite. One approach is to introduce a ceramic powder to create a composite with relative permittivity values of up to 10 5 reported in some composite systems . Though, high loading levels of ceramic fillers are usually needed in order to realize high enough permittivity and in such a case, the composites exhibit deteriorated physical and processing properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conventional process typically used to increase the dielectric permittivity is by introducing electrical conductivity or incorporating conductive fillers into the polymer matrix to form a composite. One approach is to introduce a ceramic powder to create a composite with relative permittivity values of up to 10 5 reported in some composite systems . Though, high loading levels of ceramic fillers are usually needed in order to realize high enough permittivity and in such a case, the composites exhibit deteriorated physical and processing properties.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to introduce a ceramic powder to create a composite with relative permittivity values of up to 10 5 reported in some composite systems. [27][28][29][30][31] Though, high loading levels of ceramic fillers are usually needed in order to realize high enough permittivity and in such a case, the composites exhibit deteriorated physical and processing properties. It is common for publications related to the manufacture and characterization of these high-permittivity composites to highlight their potential application as multilayer and small-volume highperformance capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…6 Up to now, similar CP results have been reported in rutile TiO 2 ceramics by co-doping acceptor ions (trivalent ions: Al, Ga, In, or rare earth ions; bivalent ions: Zn, or alkaline-earth ions) and donor elements (pentavalent ions: Nb or Ta). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Most of those reports are convinced of the formation of electronpinned defect-dipole (EPDD), while other mechanisms have also been proposed including interface effect arising from internal barrier layer capacitor (IBLC) effect, 10,22 electrode effect, 11 hopping conductivity, 23 surface barrier layer effect 24 and microscopic inhomogeneities and polaronic relaxation. 25 It seems a prerequisite to achieve CP and low dielectric loss via the simultaneous incorporation of acceptor and donor substitutions into TiO 2 , although the mechanism is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, giant permittivity materials with a large dielectric constant ( ε r ), low dielectric loss (tanδ), and good thermal stability have attracted much attention due to the requirements for the miniaturization of electronic devices and high‐energy storage capacitors . In 2013, the remarkable dielectric behavior of the materials, In and Nb codoped TiO 2 ‐based ceramics, was reported by Liu et al; these materials showed low dielectric loss (<5%) and large dielectric constant (~10 4 ) and had better temperature stability in the range from 80 to 450 K. Meanwhile, the authors deemed that the origin of the dielectric response was attributed to the intrinsic dielectric effect, that is, the electron pinned defect dipole (EPDD).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the remarkable dielectric behavior of the materials, In and Nb codoped TiO 2 ‐based ceramics, was reported by Liu et al; these materials showed low dielectric loss (<5%) and large dielectric constant (~10 4 ) and had better temperature stability in the range from 80 to 450 K. Meanwhile, the authors deemed that the origin of the dielectric response was attributed to the intrinsic dielectric effect, that is, the electron pinned defect dipole (EPDD). Subsequently, based on the same design idea, a series of codoped TiO 2 ‐based ceramics with better dielectric properties were also obtained for other ions (Ca 2+ , Zn 2+ , Mg 2+ , Sc 3+ , Y 3+ , Al 3+ , In 3+ , Yb 3+ , etc., as acceptors and Nb 5+ , Ta 5+ , etc., as donors) …”
Section: Introductionmentioning
confidence: 99%